Efektivitas Gel Ekstrak Daun Binahong (Anredera cordifolia) 5% Terhadap Jumlah Neutrofil pada Proses Penyembuhan Luka Pasca Pencabutan Gigi Tikus strain Wistar - Azizah, Khoirunisa Ulayya; Anwaristi, Aprilia Yuanita; Kurniawati, Dwi; Ningsih, Juwita Raditya (ARTERI : Jurnal Ilmu Kesehatan, 2024)
The process of tooth extraction can cause injury and trigger healing stages involving soft tissue and alveolar bone. The stages of healing include hemostasis, inflammation, proliferation, and remodeling. The use of NSAIDs for wound healing can cause side effects, so it is necessary to look for alternatives such as binahong leaf gel extract. To determine the effectiveness of 5% concentration of binahong leaf extract gel on the number of neutrophils in wound healing after tooth extraction in Wistar rats. This study is expected to be a foundation for the development of further research on alternative treatments using 5% binahong leaf gel extract in the process of healing wounds after tooth extraction. This type of research is a laboratory experiment with a post test only control group approach. The research subjects consisted of 27 jaw preparations of Wistar strain rats which were divided into three types of treatments, namely CMC-Na 1% as negative control, povidone iodine 1% as positive control, and 5% binahong leaf extract gel as treatment. Data analysis was performed using One Way ANOVA test and Post Hoc LSD test. There was a significant difference between the binahong and poviode iodine groups, as well as the binahong and CMC-Na groups with p-value <0.05. The mean difference values between the treatment group and the positive control were -18.267 (day 3), -7.200 (day 5), and -5.733 (day 7). While between the treatment group and the negative control were -11.933 (day 3), -17.533 (day 5), and -13.067 (day 7). 5% concentration of binahong (Anredera cordifolia) leaf extract gel is more effective than CMC-Na and povidone iodine to heal wounds after tooth extraction.